An embodied exercise to address HIV- and tuberculosisrelated stigma of healthcare workers in Southern Africa. (1st April 2019) - Yassi, Annalee; Mabhele, Simphiwe; Wilcox, Elizabeth S.; Tsang, Vivian W. L.; Lockhart, Karen
Healthcare workers (HCW) face the risk of occupational exposure to infectious diseases, especially in countries with high burdens of tuberculosis (TB) and human immunodeficiency virus (HIV). Disclosure of TB and/or HIV status is needed to ensure prompt action and treatment, and, in the case of TB, prevent transmission to co-workers and patients. Traditional education and training has had limited impact. It is known that stigma plays a major role in hindering disclosure of HIV status and accessing treatment. Participatory theatre has been used to cultivate communication skills and empathy. We therefore incorporated an embodied stigma exercise into a multi-country collaboration, in which we brought 78 HCWs from seven hospitals to one of three workshops in South Africa, Mozambique and Zimbabwe, respectively. We describe the exercise, highlight the skilled facilitation needed and present results from exit evaluations and interviews with participants. Some changes in attitudes were noted and our observations provide a basis for considering use of embodied methods in efforts to reduce workplace stigma.